Conductive paste, solar cell prepared therefrom, and manufacturing method
By using conductive paste mixed with tellurium-based glass and lead germanate-based glass, the problem of difficulty in improving the bond strength and contact resistance of the solar cell electrode are solved, and the effects of high stability and high conversion efficiency are achieved.
Patent Information
- Application Number
- CN202110246716.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-05
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-03-05
AI Technical Summary
When the existing solar cells form the light-receiving electrode, it is difficult to ensure that the bonding strength and contact resistance between the semiconductor substrate and the electrode are reduced at the same time, which affects the conversion efficiency and stability of the battery.
A conductive paste composed of a mixture of tellurium-based glass and lead germanate-based glass is used to form a light-receiving surface electrode on the semiconductor substrate by screen printing, and an anti-reflection film is removed during the sintering process to form a good ohmic contact.
High stability, good ohmic contact and high conversion efficiency of solar cell electrodes are achieved, and the problem of poor EL detection is avoided.
Smart Images

Figure CN115019997B_ABST
Abstract
Description
Technical Field
[0001] The present invention mainly relates to a slurry composition suitable for manufacturing a solar cell electrode which is defect-free under EL detection and has high stability, a solar cell using the slurry and a manufacturing method thereof. Background Art
[0002] Conventional solar cells are formed by setting a semiconductor layer of opposite conductivity on a conductive semiconductor substrate, and setting an anti-reflection film and a light-receiving surface electrode on the semiconductor layer, and setting a back electrode structure on the back (hereinafter referred to as "electrode" when the front and back are not distinguished). The electric energy generated by the pn junction of the semiconductor after receiving light is extracted through the electrode. Assuming that the above-mentioned semiconductor substrate is a p-type polycrystalline semiconductor silicon substrate, the semiconductor layer on the light-receiving side is an n+ layer, and at the same time, assuming that the semiconductor layer on the back side is a p+ layer, the above-mentioned anti-reflection film can reduce the surface reflectivity and increase the light receiving rate while maintaining sufficient visible light transmittance, so it is generally composed of thin films such as silicon nitride, titanium dioxide, and silicon dioxide. Solar cells with multi-layer structures are now also widely popular, such as a cell structure with a protective layer (passivation layer, generally composed of aluminum oxide, silicon oxide, etc.) that improves efficiency by protecting the semiconductor layer under the anti-reflection film, and a cell structure called TOPCON (Tunneling oxide passivated contact) with a conductive layer under the semiconductor layer.
[0003] At the same time, there are also bifacial solar cells whose back side can absorb sunlight just like the front side.
[0004] The above-mentioned anti-reflection film (including both with and without a protective layer if not specifically marked) has a large resistance value, and in order to more fully extract the electrical energy generated by the semiconductor pn junction, it is necessary to remove the anti-reflection film from the portion where the light-receiving surface electrode is formed. Therefore, assuming that the light-receiving surface electrode of the solar cell is formed by a burn-through method, the above-mentioned anti-reflection film is first formed on the n+ layer, and then the conductive paste is printed on the anti-reflection film by screen printing, that is, the electrode material in the form of paste is coated and printed in a suitable shape, and then sintered. During the sintering process, the electrode material is heated and melted, and the anti-reflection film in contact with the electrode material will also melt, thereby forming contact between the light-receiving surface electrode and the semiconductor substrate. Assuming that the main components of the above conductive paste are silver powder, glass (after melting and quenching the glass raw material, it is made into glass in the form of flakes or powder after ball milling as needed), organic phase and organic solvent, during the sintering process, the glass component in this conductive paste will destroy the anti-reflection film, and the conductor component in the conductive paste will form an ohmic contact through the n+ layer. Therefore, compared with removing part of the anti-reflection film before forming the electrode, the process is simpler, and there will be no problem of alignment deviation between the part where the anti-reflection film is removed and the part where the electrode is formed.
[0005] When forming the above-mentioned solar cell light-receiving surface electrode, it is necessary to reduce the contact resistance while ensuring the bonding strength between the semiconductor substrate and the electrode, ensure good ohmic contact, and improve the conversion efficiency of the battery. In response to these requirements for solar cell electrodes, there have been many proposals and suggestions for improving bonding strength and contact resistance since a long time ago. Among them, the most effective one is the solution of using tellurium glass.
[0006] Tellurium acts as a network former in the glass composition, which can increase the amount of silver dissolved in the glass and reduce the contact resistance. In the cooling stage of sintering, it can inhibit the precipitation of silver, thereby widening the sintering window while inhibiting excessive corrosion of the semiconductor substrate.
[0007] Through the above-mentioned effects, the anti-reflection film (also called insulating film) can be fully corroded to ensure good contact between the light-receiving surface electrode and the substrate. At the same time, since the electrode material entering the semiconductor layer area such as the pn junction can be suppressed, it will be easier to form a good ohmic contact, and because the conductivity is also improved, the electrical performance should also be improved. In addition, it is easier to control burn-through, which is also helpful for thinning the semiconductor layer on the light-receiving side. Summary of the invention
[0008] In the patent disclosure WO / 2020 / 238367, the inventor provides a conductive paste, a solar cell printed with the conductive paste as a surface electrode, and a method for manufacturing the solar cell. The EL performance of the solar cell obtained is normal, the stability is high, and the battery ohmic contact is excellent. At the same time, the battery conversion efficiency is high and the bonding strength is excellent. In this patent disclosure, a method is proposed by mixing a tellurium-based glass that is substantially lead-free and has lithium bismuth telluride as an essential component, and a lead silicate-based glass that is substantially tellurium-free and has lead silicon as an essential component. Through further exploration and research, the inventor found that in addition to lead-silicon glass, lead-germanium glass can achieve the same technical effect. The advantage of using germanium is that the melting point of germanium (958.5°C) is lower than the melting point of silicon (1414°C), the glass-forming range will be wider than silicon, and there will be more free space in designing the glass formula, which is more conducive to industrial production.
[0009] The technical solution of the present invention is as follows:
[0010] A conductive paste for forming a surface electrode of a solar cell, comprising conductive powder, mixed glass, and an organic phase; wherein the mixed glass comprises the following two types of glass components: the first type of glass is selected from at least one tellurium-based glass that is substantially lead-free and has lithium bismuth telluride as an essential component; the second type of glass is selected from at least one lead germanate-based glass that has lead and germanium as essential components and is substantially tellurium-free.
[0011] The conductive paste as described above, wherein in the mixed glass, the mass ratio of the total amount of the tellurium-based glass to the total amount of the lead germanate-based glass is 2:8 to 8:2.
[0012] The conductive paste as described above, wherein the tellurium-based glass contains 44 to 76 mol %, 7 to 51 mol % bismuth, and 2 to 14 mol % lithium in terms of oxides.
[0013] In some embodiments of the present invention, the tellurium glass may further contain any one or more of oxides of tungsten, zinc, silicon, sodium, aluminum, and copper.
[0014] The conductive paste as described above, wherein the lead germanate glass may also contain any one or more of zinc, tungsten, sodium, lithium, aluminum, copper, molybdenum, magnesium, titanium, chromium, manganese, and bismuth. The lead germanate glass, converted into oxides, comprises 39 to 70 mol% of lead, 20 to 60 mol% of germanium, and 0 to 20 mol% of zinc, tungsten, sodium, lithium, aluminum, copper, molybdenum, magnesium, titanium, chromium, manganese, and bismuth in total.
[0015] The conductive paste as described above, wherein, without affecting the purpose of the present invention, for example as an alternative embodiment of the main embodiment of the present invention, the mixed glass may also contain other types of glass. In this case, for the mixed glass with a mass of 100%, the total mass of the first type of glass and the second type of glass exceeds 50%.
[0016] In the conductive paste as described above, the content of the mixed glass is preferably controlled to be about 0.1 to 10 mass parts per 100 mass parts of the conductive powder.
[0017] The present invention also provides a solar cell, which comprises a semiconductor substrate, an anti-reflection film disposed in a first region on the surface of the semiconductor substrate, and a surface electrode disposed in a second region on the surface of the semiconductor substrate, wherein the surface electrode is printed by any of the above-mentioned conductive pastes. The above-mentioned surface refers to the front side and / or the back side of the semiconductor substrate.
[0018] The present invention also provides a method for manufacturing a solar cell, wherein the solar cell comprises a semiconductor substrate, an anti-reflection film disposed in a first region on the surface of the semiconductor substrate, and a surface electrode disposed in a second region on the surface of the semiconductor substrate, wherein the manufacturing method is mainly divided into the following three steps:
[0019] The first process step is: forming an anti-reflection film on the surface of the semiconductor substrate;
[0020] The second process step is: printing a conductive paste containing conductive powder, mixed glass, and organic phase on the anti-reflection film formed in the first step, wherein the mixed glass is mainly composed of a type of tellurium-based glass that is substantially lead-free and contains lithium bismuth telluride as an essential component and a type of lead germanate-based glass that is substantially tellurium-free and contains lead germanium as an essential component;
[0021] The third step of the process is: sintering the conductive paste, during which the anti-reflection film portion located under the conductive paste is removed, thereby ultimately forming the anti-reflection film in the first area of the semiconductor substrate and the surface electrode in the second area of the semiconductor substrate.
[0022] The above-mentioned surface refers to the front side and / or the back side of the semiconductor substrate.
[0023] As described above, the first type of glass may include one or more tellurium-based glasses that are substantially lead-free and contain lithium bismuth telluride as essential components; the second type of glass may include one or more lead germanate-based glasses that are substantially tellurium-free and contain lead and germanium as essential components.
[0024] The present invention also claims a glass material for solar cells, which is any of the above-mentioned mixed glasses. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a cross-sectional view of an important part of an embodiment of a solar cell manufactured using the conductive paste related to the present invention;
[0026] Figure 2 This is an enlarged planar pattern diagram of the light-receiving electrode side;
[0027] Figure 3 This is an enlarged bottom schematic diagram of the back electrode side;
[0028] The meanings of the numbers in the figure are as follows: 1—semiconductor substrate; 1a—n-type semiconductor layer; 1b—p-type semiconductor layer; 2—anti-reflection film (including or excluding protective layer); 3—light-receiving surface electrode; 4—back electrode; 5a, 5b...5n—fine gate electrode; 6—main gate electrode; 7—collecting electrode; 8—lead-out electrode. DETAILED DESCRIPTION
[0029] The present invention is based on the above discovery of the inventors. The conductive paste involved in the present invention is a conductive paste for forming solar cell electrodes, which is characterized by using at least conductive powder, and lead-free glass whose main component is lithium bismuth telluride and substantially does not contain lead, and lead germanate glass whose main component is lead germanium and substantially does not contain tellurium.
[0030] In this article, the range expressed by "a value to another value" is a summary expression method to avoid listing all the values in the range one by one in the specification. Therefore, the description of a specific numerical range covers any value in the numerical range and a smaller numerical range defined by any value in the numerical range, just as if the arbitrary value and the smaller numerical range were explicitly written in the specification.
[0031] The following will describe the embodiments of the present invention in detail. It should be understood that these embodiments and examples are only used to illustrate the present invention, and are not intended to limit the scope of protection of the present invention. In practical applications, improvements and adjustments made by those skilled in the art according to the present invention still belong to the scope of protection of the present invention.
[0032] Figure 1 It is a cross-sectional view of an important part of the morphology of a solar cell manufactured using the conductive paste related to the present invention.
[0033] The solar cell comprises: a semiconductor substrate 1 with silicon as the main component, an anti-reflection film 2 and a light-receiving surface electrode 3 formed on one surface of the semiconductor substrate 1, and a back electrode 4 formed on the other surface of the semiconductor substrate 1.
[0034] More specifically, the semiconductor substrate 1 includes a p-type semiconductor layer 1 b and an n-type semiconductor layer 1 a , and the n-type semiconductor layer 1 a is formed on the p-type semiconductor layer 1 b .
[0035] Specifically, for example, the semiconductor substrate 1 can be obtained by diffusing impurities on one surface of a p-type semiconductor layer 1b of single crystal silicon or polycrystalline silicon and forming a thin n-type semiconductor layer 1a. However, for the present invention, as long as the n-type semiconductor layer 1a can be formed on the p-type semiconductor layer 1b, there are no special restrictions or requirements on its structure and manufacturing method. In addition, the semiconductor substrate 1 can also use a structure in which a thin p-type semiconductor layer is formed on one surface of an n-type semiconductor layer, or a structure in which a p-type semiconductor layer and an n-type semiconductor layer are simultaneously formed on one surface of the semiconductor substrate 1. Regardless of the structure, as long as the anti-reflection film 2 is formed on the surface of the semiconductor substrate 1, the conductive paste involved in the present invention can be used.
[0036] In addition, Figure 1 In the figure, the surface of the semiconductor substrate 1 is flat, but in order to confine the sunlight in the semiconductor substrate as efficiently as possible, its surface actually has a tiny concave-convex structure.
[0037] The anti-reflection film 2 is formed of insulating materials such as silicon nitride (SiNx) to suppress the reflection of sunlight shown by arrow A on the light-receiving surface, thereby quickly and efficiently transmitting sunlight to the semiconductor substrate 1. The constituent materials of the anti-reflection film 2 are not limited to the above-mentioned silicon nitride, and other insulating materials may also be used, such as silicon oxide, titanium oxide, or two or more insulating materials may be used at the same time. In addition, for the semiconductor substrate, as long as it is a crystalline silicon system, either single crystal silicon or polycrystalline silicon can be used. In the present invention, the anti-reflection film 2 may or may not include a protective layer (a passivation layer that improves efficiency by protecting the semiconductor layer under the anti-reflection film, generally composed of aluminum oxide, silicon oxide, etc.).
[0038] The light-receiving surface electrode 3 is formed by penetrating the anti-reflection film 2 on the semiconductor substrate 1. The light-receiving surface electrode 3 is formed by applying the conductive paste of the present invention described later on the semiconductor substrate 1 to form a conductive film using a method such as screen printing, and then sintering. That is, during the sintering process of forming the light-receiving surface electrode 3, the anti-reflection film 2 under the conductive film is decomposed, removed, and burned through, so that the conductive paste and the anti-reflection film 2 are connected together, and the light-receiving surface electrode 3 is formed on the semiconductor substrate 1, wherein the light-receiving surface electrode 3 is conductive to the semiconductor substrate 1.
[0039] The specific structure of the light-receiving surface electrode 3 can be as follows Figure 2As shown, many fine gate electrodes 5a, 5b, ... 5n are arranged together like the teeth of a comb, and the main gate electrode 6 and the fine gate electrodes 5a, 5b, ... 5n are arranged in a cross shape, and the fine gate electrodes 5a, 5b, ... 5n and the main gate electrode 6 are electrically connected. In addition, an anti-reflection film 2 is formed in the area outside the light-receiving surface electrode 3. In this way, the electric energy generated by the semiconductor substrate 1 is collected by the fine gate electrodes 5a, 5b, ... 5n, and is led out to the outside through the main gate electrode 6.
[0040] The back electrode 4 is as follows Figure 3 As shown, it is composed of a collector electrode 7 made of Al or the like formed on the back of the p-type semiconductor layer 1b, and a lead-out electrode 8 made of Ag or the like that conducts current with the collector electrode 7. The electric energy generated by the semiconductor substrate 1 is collected by the collector electrode 7, and then the electric energy is led out by the lead-out electrode 8.
[0041] Next, the conductive paste for forming the light-receiving surface electrode 3 in the present invention will be described in detail.
[0042] The conductive paste mentioned in the present invention is mainly composed of conductive powder, mixed glass and organic phase, wherein the mixed glass contains two types of glass materials, one of which is at least one type of tellurium-based glass that is substantially lead-free and has lithium bismuth telluride as an essential component, and the other type is at least one type of lead germanate-based glass that is substantially tellurium-free and has lead germanium as an essential component.
[0043] The conductive paste as described above, wherein the first type of glass may include one or more tellurium-based glasses that are substantially lead-free and have lithium bismuth telluride as an essential component; the second type of glass may include one or more lead germanate-based glasses that have lead and germanium as essential components and are substantially tellurium-free. In the following detailed table, if the specific constituent components of each element of each glass are not recorded, then the element is included in the glass as an oxide. Therefore, to say that a certain component X is "substantially free of" means that a small amount of component X is inevitably contained, or it is not excluded that a small amount of component X will be added without affecting the purpose of the present invention in order to utilize the essence of the present invention.
[0044] In addition, the conductive paste forming the light-receiving surface electrode 3 contains the above-mentioned conductive powder, mixed glass, appropriate additives and organic phase. This conductive paste can also be a rheological paste, coating, or ink-like composition suitable for other printing methods besides screen printing.
[0045] The content of mixed glass in the conductive paste can refer to the usual amount used in the conductive paste for solar cell electrodes, but here is an example. For a conductive powder with a mass of 100, the content of mixed glass is preferably controlled to be about 0.1 to 10. For a conductive powder with a mass of 100, if the mass of the mixed glass is above 0.1, the specified sealing and electrode strength can be obtained. In addition, for a conductive powder with a mass of 100, if the mass of the mixed glass is below 10, the glass will float on the surface of the electrode, and the glass flowing into the interface of the diffusion layer of the electrode and the semiconductor substrate can help reduce the increase in contact resistance. Although there are no special restrictions, the average particle size of the tellurium glass and lead germanate glass in the conductive paste in this embodiment is most suitable to be 0.5 to 3.0 μm.
[0046] There are no restrictions on the conductive powder except that the main component is silver. Its shape can be spherical, flake, dendritic, etc., and the silver powder that has been used before can be used. In addition, in addition to pure silver powder, silver-coated composite powder with at least a silver layer on the surface, or alloys with silver as the main component can be used. The average particle size of conductive powders such as silver powder is preferably 0.1 to 10 μm. In addition, two or more conductive powders with different average particle sizes, particle size distribution, shapes, etc. can be mixed and used, and even silver powder and conductive powders other than silver can be mixed and used. The above-mentioned "main component" refers to a component with a mass of more than 50%, preferably a component with a mass of more than 70%. In addition, there are no other restrictions on the metals that are composited, alloyed, or mixed with the silver powder, as long as they do not damage the effects of the present invention and its embodiments, such as aluminum, gold, palladium, copper, nickel, etc. However, from the perspective of conductivity, silver powder is still the most recommended.
[0047] There are no special restrictions on the organic phase. Generally, organic resins and organic solvents commonly used in the organic phase of silver paste are used reasonably. In addition, organic resins can use cellulose, acrylic resins, phenol resins, alkyd resins, or rosin resins. Organic solvents can use alcohols, ethers, esters, hydrocarbons and other organic solvents, or water, and mixed solvents of the above. Therefore, there are no special requirements for the proportion of the organic phase. Just take an appropriate amount, and then form a slurry with conductive powder and inorganic components such as mixed glass, and then adjust it reasonably by coating and other methods. Having said that, generally for a conductive powder with a mass of 100, the mass of the organic phase is about 5 to 40.
[0048] Other components can be added as needed, as long as they do not damage the effects of the present invention and its embodiments, and conventional additives such as plasticizers, viscosity regulators, surfactants, oxidants, metal oxides, metal organic compounds, etc. can be added in appropriate amounts. In addition, silver compounds such as silver carbonate, silver oxide, and silver acetate can also be used. In order to optimize the sintering temperature and improve the characteristics of the solar cell, copper oxide, zinc oxide, tungsten oxide, titanium oxide, etc. can also be added in appropriate amounts.
[0049] The tellurium-based glass contains, for example, 44 to 76 mol % of tellurium, 7 to 51 mol % of bismuth, and 2 to 14 mol % of lithium when converted into oxides.
[0050] In the above-mentioned tellurium-based glass, tellurium plays the role of a network former. As mentioned above, it can increase the amount of silver dissolved in the glass and reduce the contact resistance. In the cooling stage of sintering, it can inhibit the precipitation of silver, widen the sintering window, and inhibit the corrosion of the semiconductor substrate. Through these effects, the insulating film can be fully corroded to ensure good contact between the electrode material and the substrate. At the same time, since the electrode material entering the semiconductor layer area such as the pn junction can be inhibited, it will be easier to form a good ohmic contact, and the conductivity is also improved, and the electrical performance can also be improved. In addition, it is easier to control burn-through, which is also helpful for the thinning of the semiconductor layer on the light-receiving side. If the tellurium content is less than 44 (mol%), the amount of silver dissolved in the glass cannot be fully increased, and if it exceeds 76 (mol%), the corrosion inhibition effect will be too strong, and it will not be fully burn-through.
[0051] In addition, bismuth is a component that increases the softening point of glass. It can be added when adjusting the softening point while ensuring the low viscosity of tellurium-based glass. In addition, it can also give the glass a corrosive effect. Although the above-mentioned tellurium has a strong inhibitory effect on corrosion, the corrosiveness can be controlled just right by appropriately adjusting the bismuth content. However, if the bismuth content exceeds 52 (mol%), the glass will easily crystallize.
[0052] In addition, lithium has the effect of lowering the softening point of glass and is also a donor. For n-type semiconductors, the donor concentration near the interface will decrease through mutual diffusion between the semiconductor substrate (such as silicon substrate) and the electrode material, and lithium can play a replenishing role. If the lithium content is less than 1 (mol%), it will not play a good replenishing role, but if it exceeds 14 (mol%), the corrosion effect will be too strong and the stability of the glass will decrease. In addition, generally speaking, alkali metal components will have a bad effect on the characteristics of solar cells, so it is best not to use them. For example, Na will cause the opening voltage Voc to decrease, and K will cause FF to decrease while increasing contact resistance. Moreover, Na and K will not form donors, so there is no benefit in using them. Lithium has a replenishing effect, and in the formation of electrodes for n-type semiconductors, better solar cell characteristics can be obtained, so it is very useful.
[0053] In addition, tellurium-based glass may contain any one or more of oxides of tungsten, zinc, silicon, sodium, aluminum, and copper in addition to lithium bismuth telluride.
[0054] The above-mentioned lead germanate glass has lead germanium as an essential component and may also contain any one or more of zinc, tungsten, sodium, lithium, aluminum, copper, molybdenum, magnesium, titanium, chromium, manganese and bismuth.
[0055] Lead germanate glass may contain any one or more of zinc, tungsten, sodium, lithium, aluminum, copper, molybdenum, magnesium, titanium, chromium, manganese and bismuth in addition to lead germanium. The contents of each element when converted into oxides are: 39-70 mol% lead, 20-60 mol% germanium, and 0-20 mol% in total of zinc, tungsten, sodium, lithium, aluminum, copper, molybdenum, magnesium, titanium, chromium, manganese and bismuth.
[0056] Lead is mainly used as a mesh-forming component to form a network of lead germanate glass. Lead has the ability to form glass alone, and its content is preferably between 39 and 70 mol%. Within this range, the burn-through property will be improved.
[0057] Germanium, especially in the lead germanate glass, can help form a glass network and make it easier to adjust the softening point. When converted into oxides, if the content of germanium is 1 to 60 mol%, it will be easier to form a glass, and the best content range is 20 to 55 mol%. Once the content exceeds 60 mol%, the softening point will become too high, and as a mesh-forming component of lead, there is a concern that it will hinder the formation of the network.
[0058] The lead germanate glass may also contain any one or more of zinc, tungsten, sodium, lithium, aluminum, copper, molybdenum, magnesium, titanium, chromium, manganese and bismuth. The total content of these elements, when converted into oxides, is preferably less than 20 mol%.
[0059] In order to obtain a good appearance and a highly stable surface electrode in EL detection, it is best to control the mass ratio of tellurium glass and lead germanate glass in the mixed glass to 2:8 to 8:2. In addition, the mixed glass is at least a mixture of tellurium glass and lead germanate glass, and may also contain other glasses without substantially affecting the effect of the present invention.
[0060] As mentioned above, the conductive paste made of a mixed glass mainly composed of tellurium-based glass containing essentially no lead and containing lithium bismuth telluride as an essential component and lead germanate-based glass containing essentially no tellurium as an essential component can balance good ohmic contact and bonding strength, and can also form a surface electrode without EL problems. This effect cannot be achieved by using tellurium-based glass alone or lead germanate-based glass alone, and it cannot be achieved by using lead tellurium-based glass alone.
[0061] Embodiments of the present invention will be described in detail below.
[0062] Example 1
[0063] 〔Sample production〕
[0064] Making telluride glass :Prepared TeO 2 、Bi 2 O 3 , WO 3 、ZnO、Al 2 O 3 、LiO 2 , B 2 O 3 Etc., and the glass raw materials were weighed and modulated according to the ratio shown in Table 1-1, and finally made into sample glass A-1.
[0065] Table 1-1
[0066]
[0067] in,
[0068] A-1 is an example of a tellurium-based glass defined in the present invention that is substantially lead-free and contains lithium bismuth telluride as an essential component.
[0069] Making lead germanate glass :Prepared PbO, Bi 2 O 3 , WO 3 、ZnO、GeO 2 、Na 2 O.B 2 O 3 、Al 2 O 3 、LiO 2 、TiO 2The glass raw materials were weighed and adjusted in the proportions shown in Table 2-1 and Table 2-2, and finally small sample glasses B-1 to B-3 were made.
[0070] Table 2-1
[0071] B-1 PbO B2O3 GeO2 Al2O3 TiO2 Mol% 55.56 9.26 18.52 9.26 7.41
[0072] Table 2-2
[0073]
[0074] in:
[0075] B-1 and B-2 are examples of lead germanate-based glasses containing lead germanium as an essential component and containing substantially no tellurium.
[0076] B-3 is a comparative example containing no germanium.
[0077] In addition, as the conductive powder, spherical silver powder having an average particle size of 2.0 μm was prepared in advance.
[0078] Preparation of organic phase: 10 wt% ethyl cellulose was used as resin, and 90 wt% octanol was used as organic solvent, and the two were mixed to prepare the organic phase.
[0079] Then, take 88.0wt% silver powder and 2.6wt% total glass, mix them with rheology adjusters such as fatty acid amide, fatty acid, and the above-mentioned organic phase, mix them with a planetary mixer, and then mix and press them with a three-roll mill to make a conductive paste.
[0080] The method for making a solar cell using each of the conductive pastes prepared above is as follows:
[0081] A single crystal silicon solar cell Si-based semiconductor substrate (156 mm square) was purchased from Huachang Company in China. The silicon semiconductor substrate has a textured surface, a square resistance of 90Ω / sq, and a SiNx anti-reflection film on the phosphorus diffused emitter layer.
[0082] We also purchased monocrystalline silicon solar cell Si-based semiconductor substrates (156 mm square) from China's Tongwei Company. The silicon semiconductor substrates also have a textured surface and a square resistance of 90Ω / sq. It has a protective layer of atomic layer deposited aluminum oxide (ALD-Al2O3) on the phosphorus diffused emitter layer and a SiNx anti-reflection film on the protective layer.
[0083] Next, prepare aluminum paste with Al as the main component and silver paste with Ag as the main component. Then apply appropriate amount of aluminum paste and silver paste on the back of the above-mentioned Si-based semiconductor substrate, and then dry and bake to form a conductive film for the back electrode.
[0084] Next, the conductive paste is screen-printed to apply the conductive paste on the surface of the Si-based semiconductor substrate to form a conductive film for a light-receiving surface electrode.
[0085] The screen used for printing is a 5-main-grid screen.
[0086] After printing, a belt near-infrared furnace (manufactured by Despatch, integrated drying and sintering) was used to complete drying and sintering according to the conditions in Table 3 below.
[0087]
Table 3
[0088]
[0089] [Sample Evaluation]
[0090] The sintered solar cells are tested using an EL tester (produced by Geonic Automation), and the cells without black spots (black spots represent poor EL) in the photo test are tested for cell conversion efficiency using an IV tester (produced by Pasan). If there are no broken cells during the preparation process, 10 cells will be tested for each sample.
[0091] The adhesive strength was tested by a homemade automatic tensile testing machine using the 180-degree peeling method.
[0092] Table 4 shows the glass ratio in the slurry and the test results.
[0093] Table 4
[0094] Slurry No. Lead-free tellurium glass Ratio (wt%) Lead Germanate Glass Ratio (wt%) EL test results Battery conversion efficiency (%) 1 A-1 1.625 B-1 0.975 OK 20.00 2 A-1 1.625 B-2 0.975 OK 20.10
[0095] In Table 4, in the EL test result column, NG represents a poor test result.
[0096] When B-1 (lead germanate glass of the present invention) is combined with A-1 (lithium bismuth telluride lead-free glass of the present invention) (No. 1), the EL detection effect is good, and when combined with B-2 (No. 2), the EL detection result is still good.
[0097] It can be seen that for the lead germanate glass represented by the B series, germanium and lead elements are essential.
[0098] Since B-3 cannot form glass, we can conclude that germanium is an essential element.
[0099]
Industrial Applicability
[0100] The solar cell produced by using the conductive paste of the present invention as electrode paste has good electrical performance (cell conversion efficiency) and bonding strength, and EL detection shows good contact and high stability.
[0101] Under the guidance of the present invention and the above-mentioned embodiments, it is easy for those skilled in the art to foresee that each raw material or its equivalent substitute, each processing method or its equivalent substitute listed or exemplified in the present invention can realize the present invention, and the upper and lower limit values and interval values of the parameters of each raw material and processing method can realize the present invention, and the embodiments are not listed one by one here.
Claims
1. A conductive paste for forming a surface electrode of a solar cell, characterized in that: Containing conductive powder, mixed glass, and an organic phase; wherein the mixed glass comprises the following two types of glass components: the first type of glass is selected from at least one of tellurium-based glasses that are substantially lead-free and contain lithium bismuth telluride as an essential component; the second type of glass is selected from at least one of lead germanate-based glasses that contain lead and germanium as essential components and are substantially tellurium-free; and, In the mixed glass, the mass ratio of the total amount of the tellurium series glass to the total amount of the lead germanate series glass is 2:8 to 8:2; The tellurium-based glass, converted into oxides, contains 44-76 mol% tellurium, 7-51 mol% bismuth, and 2-14 mol% lithium; The lead germanate glass, converted into oxides, comprises 39 to 70 mol % of lead, 20 to 60 mol % of germanium, and 0 to 20 mol % of zinc, tungsten, sodium, lithium, aluminum, copper, molybdenum, magnesium, titanium, chromium, manganese and bismuth in total.
2. The conductive paste according to claim 1, wherein For the conductive powder with a mass of 100, the content of the mixed glass is controlled to be 0.1 to 10 by mass.
3. A solar cell comprising a semiconductor substrate, an antireflection film provided in a first region on a surface of the semiconductor substrate, and a surface electrode provided in a second region on the surface of the semiconductor substrate, wherein: The surface electrode is made by printing the conductive paste described in any one of claims 1-2.
4. A method for manufacturing a solar cell, the solar cell comprising a semiconductor substrate, an antireflection film provided in a first region on a surface of the semiconductor substrate, and a surface electrode provided in a second region on the surface of the semiconductor substrate, wherein: The manufacturing method is mainly divided into the following three steps: The first process step is: forming an anti-reflection film on the surface of the semiconductor substrate; The second step is to print a conductive paste containing conductive powder, mixed glass and organic phase on the anti-reflection film formed in the first step, wherein the mixed glass is mainly composed of a type of tellurium-based glass that is substantially lead-free and has lithium telluride, bismuth and lithium as essential components and a type of lead germanate-based glass that is substantially tellurium-free and has lead germanium as essential components; in the mixed glass, the mass ratio of the total amount of the tellurium-based glass to the total amount of the lead germanate-based glass is 2:8-8:2; the tellurium-based glass, when converted into oxides, contains 44-76 mol% of tellurium, 7-51 mol% of bismuth and 2-14 mol% of lithium; the lead germanate-based glass, when converted into oxides, contains 39-70 mol% of lead, 20-60 mol% of germanium and 0-20 mol% of zinc, tungsten, sodium, lithium, aluminum, copper, molybdenum, magnesium, titanium, chromium, manganese and bismuth in total; The third step of the process is: sintering the conductive paste, during which the anti-reflection film portion located under the conductive paste is removed, thereby ultimately forming the anti-reflection film in the first area of the semiconductor substrate and the surface electrode in the second area of the semiconductor substrate.
5. A glass material for solar cells, characterized in that: The mixed glass used in the conductive paste according to any one of claims 1 to 2.
Citation Information
Patent Citations
Conductive paste, solar cell prepared from conductive paste and manufacturing method
CN111902881A